Magnetic switching modes for exchange spring systems ErFe2/YFe2/DyFe2/YFe2 with competing anisotropies - Zimmermann, J; Martin, K; Bordignon, G; Franchin, M; Ward, R; Bowden, G; de Groot, P; Fangohr, H (2009)
The magnetization reversal processes of [10 nm ErFe2 / n YFe2 / 4 nm DyFe2 / n YFe2] multilayer films with a (1 1 0) growth axis and a variable YFe2 layer thickness n are investigated. The magnetically soft YFe2 compound acts as a separator between the hard rare earth (RE) ErFe2 and DyFe2 compounds, each of them bearing different temperature dependent magnetic anisotropy properties. Magnetic measurements of a system with n = 20 nm reveal the existence of three switching modes: an independent switching mode at low temperatures, an ErFe2 spin flop switching mode at medium high temperatures, and an YFe2 dominated switching mode at high temperatures. The measurements are in qualitative agreement with the findings of micromagnetic simulations which are used to illustrate the switching modes. Further simulations for a varied YFe2 layer thickness n ranging from 2 to 40 nm are carried out. Quantitative criteria are defined to classify the reversal behavior, and the resultant switching modes are laid out in a map with regard to n and the temperature T. A new coupled switching mode emerges above a threshold temperature for samples with thin YFe2 separation layers as a consequence of the exchange coupling between the magnetically hard ErFe2 and DyFe2 layers. It reflects the increasing competition of the two conflicting anisotropies to dominate the magnetic switching states of both RE compounds under decreasing n. © 2009 Elsevier B.V. All rights reserved.